2016
DOI: 10.1152/advan.00022.2016
|View full text |Cite
|
Sign up to set email alerts
|

Performance in physiology evaluation: possible improvement by active learning strategies

Abstract: The evaluation process is complex and extremely important in the teaching/learning process. Evaluations are constantly employed in the classroom to assist students in the learning process and to help teachers improve the teaching process. The use of active methodologies encourages students to participate in the learning process, encourages interaction with their peers, and stimulates thinking about physiological mechanisms. This study examined the performance of medical students on physiology over four semeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 15 publications
4
28
0
4
Order By: Relevance
“…The researcher further concluded that students not only learned more, but also enjoyed the activities. Although Montrezor's (2016) learning strategies did not include jigsaw cooperative learning in the study, as an active learning strategy, it should yield similar results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher further concluded that students not only learned more, but also enjoyed the activities. Although Montrezor's (2016) learning strategies did not include jigsaw cooperative learning in the study, as an active learning strategy, it should yield similar results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much research has been done on active learning in general, and it has been found that student performance improved (Russell et al, 2016) and that students enjoyed the varying activities. One study in a physiology course (Montrezor, 2016) utilized various active learning activities such as a board game, a puzzle, a video, and a debate. The results were compared with those of classes where active methodologies were not used.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Os quizzes foram aplicados em plataforma Moodle, e forneciam feedbacks aos alunos. Observou-se aumento da motivação e do rendimento (notas) dos alunos participantes.Com relação ao portfólio, os resultados positivos em relação ao método estão de acordo com os estudosde Cotta et al (2012) Montrezor (2016),. que relataram uma melhora no desempenho e satisfação dos alunos com o uso de estratégia semelhante.Um dos objetivos do portfólio é ajudar o estudante a aprender avaliar o seu próprio trabalho(FERRAZ JÚNIOR et al, 2016).SegundoFrota et al (2011) o portfólio funcionou como um instrumento facilitador do processo de ensino-aprendizagem, sendo bem aceito pelos alunos e pelos professores, e empregado com sucesso no ensino odontológico.…”
unclassified
“…A escolha do tipo de jogo educativo a ser utilizado na proposta de treinamento depende do assunto a ser tratado e dos objetivos de aprendizagem que devem ser alcançados após a aplicação da intervenção (JONES et al, 2015). O jogo de tabuleiro, do inglês "board game", tem se mostrado uma importante ferramenta de aprendizagem para estudantes da área da saúde quando comparado a outros métodos lúdicos de ensino, como por exemplo, o quebra-cabeça (MONTREZOR, 2016). Entretanto, as evidências disponíveis sobre a relevância dos jogos de tabuleiro como aliado do processo ensino-aprendizagem e da educação permanente em saúde ainda são limitadas e merecem ser melhor investigadas, sobretudo quanto ao seu impacto na prática clínica e na promoção do conhecimento, tanto em curto como em longo prazo (KAWAMURA et al, 2014;BUKOWSKI et al, 2016;KARBOWNIK et al, 2016;MOUTON et al, 2017).…”
Section: Jogos Educativos Como Estratégia De Ensino-aprendizagem No Cunclassified